Analysts in The Development of Food and Beverage Product That is Impact to The Supply Chain Aspect in PT. Aerofood ACS Garuda Indonesia - Yohana Ditya Puspita; Mustika Putri Fatimah Ardiyanti; Mariam Nasser (AIBPM Publisher, 2018)
In this study aimed to develop of food and beverage product that is impact to the supply chain aspect in PT. Aerofood ACS Garuda Indonesia. The focus of this project is to develop the ability of the company to know the taste and flavor that were demanded from the consumer of their food and beverage product. Qualitative data were collected from public reports, articles, and journal. The contribution this paper offers is the way we could do to know, if PT. Aerofood ACS Garuda Indonesia products is acceptable to the consumer. In this project, we are focusing on the consumer of PT. Aerofood whom was from passenger of airplane in Indonesia.